Proceedings of the 2011 International Conference on Informatics, Cybernetics, and Computer Engineering (ICCE2011) November 19-20, 2011, Melbourne, Australia Volume 2: Information Systems and Computer Engineering - Jiang, Liangzhong (Advances in Intelligent and Soft Computing,, 2012)
The volume includes a set of selected papers extended and revised from the International Conference on Informatics, Cybernetics, and Computer Engineering. An information system (IS) is any combination of information technology and people's activities using that technology to support operations, management.  Computer engineering is a discipline that integrates several fields of electrical engineering and computer science required to develop computer systems. ICCE 2011 Volume 2 is to provide a forum for researchers, educators, engineers, and government officials involved in the general areas of Information system and Software Engineering to disseminate their latest research results and exchange views on the future research directions of these fields. 81 high-quality papers are included in the volume. Each paper has been peer-reviewed by at least 2 program committee members and selected by the volume editor.